Heavy metals concentrations in parsley (Petroselinum crispum) vegetable - Milad Sheydaei (Food Science and Engineering Research)
With the increase of pollutants in recent years, the environment has been exposed to serious pollution. Heavy metals (HMs) can be considered a potential risk to human health. Furthermore, soil contamination with HMs leads to their transfer to plants and animals and ultimately to humans. Due to their toxic nature, very trace amounts of them can cause serious problems. HMs are one of the important pollutants that are released from various sources. They are very harmful to the environment and health due to their toxicity, stability, and accumulation properties. In this research, the content of HMs in parsley (Petroselinum crispum) has been investigated. For this purpose, HMs such as arsenic (As), cadmium (Cd), lead (Pb), and mercury (Hg) were investigated in samples collected from local farms in the Tustan region (Lahijan city, Guilan province, Iran). According to the results, all the samples contain HMs above the standard. HMs can cause serious health problems, therefore monitoring food products is very important.